Analysis of aquifers, humidity levels with geoelectric resistivity value, and NDW Index in the geothermal area of North Langowan - Wowor, Bella M.; Manoppo, Fabian J.; Riogilang, Herawaty (AQUATIC SCIENCE & MANAGEMENT, 2021)
This research was conducted to examine the condition (location, depth, and thickness) of the aquifer, to assess the humidity level using the NDW index, and to determine the relationship between aquifer conditions and the sustainability of the geothermal system using the geoelectrical method of resistivity in the North Langowan geothermal area. The comparison between rock layer resistivity data and spectral values based on geological-hydrogeological maps was carried out to determine the relationship between aquifer conditions and humidity levels in the geothermal area to the continuity of the geothermal system in the Tompaso region. The data was processed using IP2WIN and ILWIS programs. The results showed that at the research site there were semi-confined aquifers and free aquifers, which were indicated by low resistivity values. It can be concluded that the aquifer in the North Langowan geothermal area was at a depth ranging from 0 m to 16 m with a thickness ranging from 3.98 to 12 m, moderate wetness, and has a good relationship in supporting the continuity of the Tompaso geothermal system.Indonesian title:Â Analisis akuifer, tingkat kelembaban dengan nilai resistivitas geolistrik, dan Index NDW di daerah panas bumi Langowan UtaraÂ